Molecular Relaxations in Magnesium Polymer Electrolytes via GHz Broadband Electrical Spectroscopy. Issue 11 (18th September 2013) - Piccolo, Michele; Giffin, Guinevere A.; Vezzù, Keti; Bertasi, Federico; Alotto, Piergiorgio; Guarnieri, Massimo; Di Noto, Vito
Abstract GHz broadband electrical spectroscopy (G‐BES) is adopted to investigate the molecular relaxations and interactions occurring within the system in an oxygen‐ and water‐free atmosphere in the 300 kHz–20 GHz and −40 to 250 °C frequency and temperature ranges, respectively. A new electrolyte for magnesium secondary batteries that can transfer magnesium ions efficiently is presented. This electrolyte is based on polyethylene glycol 400 and a polymeric form of δ‐MgCl2. The information obtained by G‐BES is crucial for studying the conduction mechanism of these new electrolytes.